New data on dracunculoid nematodes from fishes off New Caledonia, including four new species of Philometra (Philometridae) and Ichthyofilaria (Guyanemidae) - Moravec, Frantisek; Justine, Jean-Lou (Folia parasitologica, 2009)
Recent examinations of newly obtained materials of dracunculoid nematodes (Dracunculoidea) parasitizing marine fishes off New Caledonia, South Pacific, revealed the presence of several nematodes of the genera Philometra Costa, 1845 (Philometridae) and Ichthyofilaria Yamaguti, 1935 (Guyanemidae), including the following four new species: Philometra priacanthi sp. n. (males) from the gonads of Priacanthus hamrur (Forsskål) (Priacanthidae), Philometra tenuicauda sp. n. (male and mature and gravid females) from the gonads of Lagocephalus sceleratus (Gmelin) (Tetraodontidae), Philometra dentigubernaculata sp. n. (males) from the oculo-orbit of Tylosurus crocodilus (Péron et Lesueur) (Belonidae), and Ichthyofilaria novaecaledoniensis sp. n. (subgravid female) from the musculature of Hoplichthys citrinus Gilbert (Hoplichthyidae). The new species are characterized mainly by the length and structure of spicules and the gubernaculum, body size, location in the host and by the type of hosts. In addition, the findings of Philometra lethrini Moravec et Justine, 2008 from the gonads of Lethrinus miniatus (Forster) and L. variegatus Valenciennes (both Lethrinidae) represent new host records for this parasite; for the first time, its subgravid females were found to be up to 350 mm long. The occurrence of Philometra ocularis Moravec, Ogawa, Suzuki, Miyazaki et Donai, 2002 in the oculo-orbit of Epinephelus areolatus (Forsskål) (Serranidae) off New Caledonia was confirmed.
Keywords: ryby; Nová Kaledonie; hlístice; Fishes; Nematode Infections; Male; Fish Diseases; Larva; larva; Animals; New Caledonia; Female; mužské pohlaví; ženské pohlaví; Nematoda; nematodózy; zvířata; nemoci ryb